The Concept Of Morality In The Qur'an And Its Influence On Mental Health - Hartawan, Hartawan; Rawzalgina, Arthi Amalia (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
This study is motivated by the urgency to reconstruct the understanding of Islamic ethics (akhlaq) based on the Qur'an, and to respond to the challenges of psychological crises through a spiritual approach. The aim of this research is to explore the concept of akhlaq in the Qur'an in depth and to explain its influence on mental health. This study employs a qualitative approach using library research methods, analyzing primary sources such as the Qur'an and classical and contemporary Tafsir, alongside secondary literature including scientific articles and previous studies. The findings reveal that Islamic akhlaq is not merely an ethical framework, but also serves as a protective mechanism that fosters psychological resilience. Individuals who embody virtuous character tend to experience greater emotional balance and mental stability, while those who exhibit immoral behavior are more susceptible to psychological distress. The novelty of this article lies in its integrative approach, bridging Qur'anic moral concepts with contemporary psychology. Here, akhlaq is positioned not only as an indicator of a healthy soul but also as an active instrument for building and restoring mental health. Consequently, these findings enrich theoretical discourse and offer practical contributions to the development of moral education and mental health policy grounded in spiritual values.